Cucullanus dogieli n. sp., a parasite of cyprinid fish - Krotas, R. (Trudy Akademii Nauk Litovskoi SSR, 1959)
Cucullanus dogieli n.sp. is described and figured. In the course of several years it has been found in Rutilus rutilus, Leuciscus leuciscus, L. cephalus, L. idus, Barbus barbus, Alburnus alburnus, Alburnoides bipunctatus, Blicca bjoerkna and Vimba vimba from the Zapadnaya Dvina, Neman, Dniester, Danube and Don. It is differentiated from C. cyprini, the only other species of this genus parasitic in cyprinids, chiefly by the shorter oesophagus (0.814 to 1.165 mm.) and spicules (0.555 to 0.627 mm.), by the larger gubernacuJum (0.087 to 0.148 mm.), and by the distribution of papillae on the male tail (there are two pairs of pre-anal, three pairs of circum-anal and five pairs of post-anal papillae). The new species is also differentiated from C. cirratus, C. heterochrous and C. incertus from marine fish.